The profiling of university of Ljubljana students according to their motives for exercise participation - Cerar Katja; Kondrič Miran; Sindik Joško (Sciendo, 2017)
The main research objective is the analysis of the grouping of the students of the University of Ljubljana, with respect to the intensity of different types of exercise participation motives, their gender, discipline and year of study, level of physical activity, status of physical education class, organization of physical activities during study, and place of residence.